Effect of Recreational Therapy on Attention and Depression in School Children with Learning Difficulties (Indian Journal of Public Health Research & Development, 2020)
Background: Learning difficulty applies to those children who have significantly greater difficulty inlearning than the majority of their age and who can’t meet the “normal” requirements of a classroom. Astudy conducted in Chandigarh gave prevalence of learning disabilities of 3-10% among student population.There were more number of boys diagnosed with specific learning disability at a high risk for problemsin attention, learning and psychological adjustment along with other associated behavioural problems.Recreational therapy utilizes leisure activities and other interest activities as interventions to address theneeds of individuals with disability as a means of recovery and well-being.Method: Forty school children with learning difficulties were selected and randomly divided in two groups.Group A subjects were given recreational therapy 4 times per week for 4 weeks and Group B subjects weregiven conventional treatment.Results: Statistically significant difference in the Moss Attention Rating Scale (MARS) scores and GlasgowDepression Scale (GDS) scores were seen between the two groups. It indicated that there was significantlyless inattention (p < 0.0001) and less depression (p = 0.0207) in the interventional group subjects.Conclusion: Evidence to support the use of recreational therapy in reducing the depression and increasingthe attention in school children with learning difficulties was provided in this study. This study will help inmanaging the associated problems like inattention and depression.Keywords: Recreational therapy, Learning Disabilities, Mandala art therapy, Clay shape art therapy,School children, Attention, Depression.
Keywords: Learning Disabilities (LD), Moss Attention Rating Scale (MARS), Glasgow Depression Scale (GDS).